Generative AI in creative workflows: A case study on Midjourney and insights for future image tools - Kim, Jhonghee; Kim, Hyungjoon (Edelweiss Applied Science and Technology, 2025)
This study evaluates the adequacy of generative AI (GenAI) image tools for future designers, specifically examining their user interfaces (UI) and user experiences (UX). Using Midjourney, a platform with 28.5 million monthly visitors, as a case study, we analyze professional designers' perceptions through surveys and interviews with 12 participants. The research identifies behavioral patterns and attitudinal changes, offering insights into user engagement. The findings aim to inform the strategic development of next-generation AI image tools, positioning them as pivotal resources in meeting the dynamic demands of the design industry.